Antidiabetic and hypolipidemic activities of Curculigo latifolia fruit: root extract in high fat fed diet and low dose STZ induced diabetic rats - Ishak, Nur Akmal; Ismail, Maznah; Hamid, Muhajir; Ahmad, Zalinah; Abd Ghafar, Siti Aisyah (Hindawi Publishing Corporation, 2013)
Curculigo latifolia fruit is used as alternative sweetener while root is used as alternative treatment for diuretic and urinary problems. The antidiabetic and hypolipidemic activities of C. latifolia fruit:root aqueous extract in high fat diet (HFD) and 40 mg streptozotocin (STZ) induced diabetic rats through expression of genes involved in glucose and lipid metabolisms were investigated. Diabetic rats were treated with C. latifolia fruit:root extract for 4 weeks. Plasma glucose, insulin, adiponectin, lipid profiles, alanine aminotransferase (ALT), gamma glutamyltransferase (GGT), urea, and creatinine levels were measured before and after treatments. Regulations of selected genes involved in glucose and lipid metabolisms were determined. Results showed the significant () increase in body weight, high density lipoprotein (HDL), insulin, and adiponectin levels and decreased glucose, total cholesterol (TC), triglycerides (TG), low density lipoprotein (LDL), urea, creatinine, ALT, and GGT levels in diabetic rats after 4 weeks treatment. Furthermore, C. latifolia fruit:root extract significantly increased the expression of IRS-1, IGF-1, GLUT4, PPARα, PPARγ, AdipoR1, AdipoR2, leptin, LPL, and lipase genes in adipose and muscle tissues in diabetic rats. These results suggest that C. latifolia fruit:root extract exerts antidiabetic and hypolipidemic effects through altering regulation genes in glucose and lipid metabolisms in diabetic rats.